Now you see it, now you don’t: On the (in)visibility of police stop and search in Northern Ireland - Topping, John (Criminology & criminal justice, 2020)
Police stop and search practices have been subject to voluminous debate for over 40 years in the United Kingdom. Yet critical debate related to the use of ‘everyday’ stop and search powers by the Police Service of Northern Ireland (PSNI) has, despite the hyper-accountable policing system of Northern Ireland, been marked by its absence. This article presents the first ever analysis of PSNI’s use of PACE-type powers (Police and Criminal Evidence (NI) Order 1989) - currently used at a higher rate and with poorer outcomes compared to the rest of the UK. While it can only be considered as an elusive power, about which detailed research evidence is markedly lacking, stop and search in Northern Ireland seems to serve as a classificatory tool for PSNI to control mainly young, socio-economically marginal male populations. The article provides new theoretical insight into stop and search as a simultaneous overt and covert practice, and speaks to wider issues of mundane police power - and practice - within highly contested and politically fractured contexts.